Molecular Determinants Regulating the Plasticity of the MHC Class II Immunopeptidome - Santambrogio, Laura (Frontiers in Immunology, 2022)
In the last few years, advancement in the analysis of the MHC class II (MHC-II) ligandome in several mouse and human haplotypes has increased our understanding of the molecular components that regulate the range and selection of the MHC-II presented peptides, from MHC class II molecule polymorphisms to the recognition of different conformers, functional differences in endosomal processing along the endocytic tract, and the interplay between the MHC class II chaperones DM and DO. The sum of all these variables contributes, qualitatively and quantitatively, to the composition of the MHC II ligandome, altogether ensuring that the immunopeptidome landscape is highly sensitive to any changes in the composition of the intra- and extracellular proteome for a comprehensive survey of the microenvironment for MHC II presentation to CD4 T cells.